Comprehensive analysis of exergy destruction sources in different engine combustion regimes. (15th April 2018) - Li, Yaopeng; Jia, Ming; Kokjohn, Sage L.; Chang, Yachao; Reitz, Rolf D.
Abstract: The exergy destruction sources of different engine combustion regimes are investigated. The results indicate that chemical reaction is the largest sources of exergy destruction. Although the exergy destruction due to chemical reaction in conventional diesel combustion (CDC) engines is the lowest, its total exergy destruction is the largest. The transition from low-temperature heat release (LTHR) to high-temperature heat release (HTHR) accumulates substantial exergy destruction, so adopting one-stage heat release fuels without LTHR is favorable to reduce exergy destruction. Higher combustion temperature benefits to reduce exergy destruction, and the required combustion temperatures to achieve the same exergy destruction fraction are different for various combustion regimes. With the increase of equivalence ratio towards the stoichiometric ratio, the exergy destruction fraction decreases due to higher combustion temperature. When the equivalence ratio exceeds the stoichiometric ratio, equivalence ratio itself plays a more negative effect, leading to larger exergy destruction fraction. Thus, the lowest exergy destruction fraction is at the stoichiometric combustion. Overall, for different combustion regimes, different strategies should be accordingly adopted to reduce exergy destruction, and effective control over the magnitude and stratification of combustion temperature is important to realize low exergy destruction, high fuel efficiency, moderate combustion rate, and low emissions simultaneously. Highlights: Chemical reaction generates the largest exergy destruction in combustion engines. Low-temperature heat release increases the exergy destruction of HCCI and RCCI. Higher combustion temperature benefits the reduction of exergy destruction. The lowest exergy destruction fraction is achieved at the stoichiometric ratio. Both low exergy destruction and NOx emissions are more easily achieved by RCCI.